WORKSHOP NERVE GLIDING EXERCISE DAN PEMBERIAN ULTRA SOUND (US) TERHADAP PENURUNAN NYERI PADA KASUS CARPAL TUNNEL SYNDROME DI GRANDMED LUBUK PAKAM - Raynald Ignasius Ginting; Sabirin Berampu; Siti Sarah Bintang; Ni Nyoman Ayu Tamala Hardis; Engraini Teja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The problem that often occurs for workers is Carpal tunnel syndrome (CTS). Carpal tunnel syndrome is a disorder of the hand due to compression of the median nerve in the carpal tunnel, either due to adhesions or abnormalities of the small bones of the hand. The median nerve innervates the thumb, index finger, middle finger and part of the ring finger, so that pain and parathesia can be felt in these areas. One way of non-pharmacological therapy that can be used in CTS is through the provision of nerve gliding exercise. Nerve gliding exercise and the administration of ultra sound (US) modality are done with the aim of reducing pressure on the wrist so that pain can be reduced. The results of this service activity stated that as many as 94% of participants as physiotherapists had understood and were able to use nerve gliding exercise and Ultra Sound (US) for pain reduction in CTS cases.